Post-traumatic osteoarthritis development is not modified by postnatal chondrocyte deletion of Ccn2 - Craig M. Keenan; Lorenzo Ramos-Mucci; Ioannis Kanakis; Peter I. Milner; Andrew Leask; David Abraham; George Bou-Gharios; Blandine Poulet (The Company of Biologists, 2020)
CCN2 is a matricellular protein involved in several crucial biological processes. In particular, CCN2 is involved in cartilage development and in osteoarthritis. Ccn2 null mice exhibit a range of skeletal dysmorphisms, highlighting its importance in regulating matrix formation during development; however, its role in adult cartilage remains unclear. The aim of this study was to determine the role of CCN2 in postnatal chondrocytes in models of post-traumatic osteoarthritis (PTOA). Ccn2 deletion was induced in articular chondrocytes of male transgenic mice at 8 weeks of age. PTOA was induced in knees either surgically or non-invasively by repetitive mechanical loading at 10 weeks of age. Knee joints were harvested, scanned with micro-computed tomography and processed for histology. Sections were stained with Toluidine Blue and scored using the Osteoarthritis Research Society International (OARSI) grading system. In the non-invasive model, cartilage lesions were present in the lateral femur, but no significant differences were observed between wild-type (WT) and Ccn2 knockout (KO) mice 6 weeks post-loading. In the surgical model, severe cartilage degeneration was observed in the medial compartments, but no significant differences were observed between WT and Ccn2 KO mice at 2, 4 and 8 weeks post-surgery. We conclude that Ccn2 deletion in chondrocytes does not modify the development of PTOA in mice, suggesting that chondrocyte expression of CCN2 in adults is not a crucial factor in protecting cartilage from the degeneration associated with PTOA. This article has an associated First Person interview with the first author of the paper.